Repräsentative Demokratie in der Krise? - Walter, Christian (Veröffentlichungen der Vereinigung der Deutschen Staatsrechtslehrer, 2013)
This volume contains presentations and discussions from a conference of the Association of German Constitutional Law Professors held in Kiel on 3-6 October 2012.